2019
DOI: 10.1111/ceo.13492
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch upregulates connexin43 in human trabecular meshwork cells

Abstract: Background Primary open angle glaucoma (POAG) patients have hallmark increases in intraocular pressure (IOP) and noted dysfunction of the trabecular meshwork (TM). Connexin43 (Cx43) is a gap junction widely expressed on the TM that is important for intercellular communication. The human gene is known as gap junction alpha‐1 (GJA1). Since the role of Cx43 in the TM is not fully understood, we set out to determine the effect of excess mechanical stretch on cultured human trabecular meshwork cells (hTMCs) and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…In a model of intestinal damage, a previous study found that intestinal damage can be significantly relieved following administration of cx43 inhibitors (32). Another study demonstrated that stretch-induced apoptosis in human trabecular meshwork cells is accompanied by upregulation of Cx43 (33). The present findings indicated that Cx43 is involved in the apoptosis of Hcy-induced H9c2 cardiomyocytes.…”
Section: Discussionsupporting
confidence: 63%
“…In a model of intestinal damage, a previous study found that intestinal damage can be significantly relieved following administration of cx43 inhibitors (32). Another study demonstrated that stretch-induced apoptosis in human trabecular meshwork cells is accompanied by upregulation of Cx43 (33). The present findings indicated that Cx43 is involved in the apoptosis of Hcy-induced H9c2 cardiomyocytes.…”
Section: Discussionsupporting
confidence: 63%
“…The subunits, which include gap junctions, are the connexins which are integral membrane proteins. In order to form the gap junctions, one connexon hemichannel, formed by six connexins, has to bond to another connexon hemichannel present on an adjacent cell [ 230 , 231 ]. The mechanical stretch in HTMCs up-regulates connexin43 (Cx43) and its isoform.…”
Section: Trabecular Meshwork (Tm) and Location Of Outflow Resistanmentioning
confidence: 99%
“…The mechanical stretch in HTMCs up-regulates connexin43 (Cx43) and its isoform. However, recently, also Cx26 and/or Cx31 have been suggested as being involved in an increased intercellular signalling related to the altered TM [ 231 ].…”
Section: Trabecular Meshwork (Tm) and Location Of Outflow Resistanmentioning
confidence: 99%
“…From the Elisa assay, we concluded that there was an increased TGF beta1 protein concentration in cell culture medium under stretch stimulation. Taking into consideration that administration of TGF beta1 exogenously into some cells can stimulate Cx43 mRNA and protein expression, while in some different cells [11,12,15,16], ad-ministration of TGF beta1 can down-regulate Cx43 expression [17,18]. Therefore, it is importance to investigate whether administration of TGF beta1 can increase or decrease Cx43 mRNA or protein expression in HUVECs.…”
Section: Increased Tgfbeta1 Mrna and Protein Level After 24 H Stretchmentioning
confidence: 99%